Identifikasi Keragaman Gen Pituitary Transcription Factor 1 (Pou1f1) pada Kambing Peranakan Etawah (Pe) di BPTU KDI-HPT Pelaihari - Suparman, A. B. P.; Mulyono, R. H.; Jakaria, Jakaria (Jurnal Ilmu Produksi dan Teknologi Hasil Peternakan, 2015)
Pituitary Tanscription Factor 1 (POU1F1) has been identified as the pituitary spesific transcription factor that regulates the expression of the growth hormone (GH) and prolactin (PRL) in the anterior pituitary. The objective of this research is identification the polymorphism of POU1F1 gene of etawah grade goat in BPTU KDI-HPT Pelaihari South Kalimantan use Polymerase Chain Reaction- Restriction Fragment Length Polymorphism (PCR-RFLP). PCR products of POU1F1 digested with Hinf1 enzyme which restric G|AnTC.  Samples are used as the material of DNA from blood samples of 115 PE goats.  POU1F1 gene amplification was performed with annealing temperature of 62 oC for 20 seconds resulting in a fragment with the length of 601 bp which is located at intron 5 and exon 6. The result of PCR-RFLP analysis indicated that the POU1F1 gene was monomorphic.  B allele had 3 fragments at 275, 243, and 83 bp respectively.